The effectiveness of therapies for dual language children with developmental language disorder: a systematic review of interventional studies. Issue 7 (9th August 2021) - Harvey, Hannah; Allaway, Hazel; Jones, Sarahjane
ABSTRACT: Purpose : This study aims to understand the effect of therapies on dual language children with developmental language disorder (DLD) on a range of bilingual language outcomes, compare with second-language-only therapy and determine whether there is any cross-linguistic transfer. Methods : A systematic review of English articles in 10 electronic databases was conducted. Screening, reviewing and appraising were performed independently by two reviewers. Quality was appraised and findings synthesised in accordance with the research questions. Results : Nine reports were identified. Five studies were found to be low in bias and therefore high in quality. Two were medium bias and two were high. Key findings were that instruction in the first language is required to support its continued acquisition and that bilingual instruction does not limit second-language growth. Conclusions : There is no identified evidence to suggest that second-language-only is better than bilingual therapy for dual language children with DLD for the development of the second language. There is evidence to suggest that bilingual therapy is equally effective for second-language development, and also supports development of the first language. Further work is required to understand the efficacious doses of both languages in order to develop cost effective therapies and achieve optimal outcomes.